2002
DOI: 10.1093/emboj/cdf438
|View full text |Cite
|
Sign up to set email alerts
|

A novel cGMP signalling pathway mediating myosin phosphorylation and chemotaxis in Dictyostelium

Abstract: Chemotactic stimulation of Dictyostelium cells results in a transient increase in cGMP levels, and transient phosphorylation of myosin II heavy and regulatory light chains. In Dictyostelium, two guanylyl cyclases and four candidate cGMP‐binding proteins (GbpA–GbpD) are implicated in cGMP signalling. GbpA and GbpB are homologous proteins with a Zn2+‐hydrolase domain. A double gbpA/gbpB gene disruption leads to a reduction of cGMP‐phosphodiesterase activity and a 10‐fold increase of basal and stimulated cGMP lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
170
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(182 citation statements)
references
References 39 publications
(46 reference statements)
12
170
0
Order By: Relevance
“…Similar defects were observed in a knockout mutant lacking the cGMP binding protein GbpC, strongly indicating that a cGMP-mediated pathway via activation of GbpC controls cortical localization and function of myosin II in chemotactic cells. 12 Our uncaging experiments clearly confirm these earlier results. They provide a direct proof that an increase in the cytosolic cGMP concentration triggers myosin II translocation to the cortex.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similar defects were observed in a knockout mutant lacking the cGMP binding protein GbpC, strongly indicating that a cGMP-mediated pathway via activation of GbpC controls cortical localization and function of myosin II in chemotactic cells. 12 Our uncaging experiments clearly confirm these earlier results. They provide a direct proof that an increase in the cytosolic cGMP concentration triggers myosin II translocation to the cortex.…”
Section: Discussionsupporting
confidence: 90%
“…18,19 Furthermore, the two large multi-domain proteins GbpC and GpcD have been characterized. 12 It was found that GbpD acts independently of intracellular cyclic nucleotides. It promotes surface attachment via lateral pseudopods and depolarization as part of a GbpD/Rap/PI3K pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro assays have shown that the cAMP-stimulated incorporation of myosin filaments into the Triton-insoluble cytoskeleton is absent in gc-null cells (Liu et al, 1993;Bosgraaf et al, 2002). To investigate the effects of the sGC protein and the cGMP product on myosin incorporation into the cytoskeleton, we coexpressed myosin-GFP in the various mutant sGC cell strains.…”
Section: Effects Of Sgc and Cgmp On Myosin Distributionmentioning
confidence: 99%
“…During chemotaxis, pseudopod formation is generally restricted to the leading edge of the cell, as myosin filaments that localize to the rear inhibit pseudopod extension (Figure 3). Cells that are defective in cGMP production or that lack the cGMP binding protein GbpC are defective in myosin assembly and are unable to suppress lateral pseudopod extension (Bosgraaf et al, 2002;Veltman and van Haastert, 2006;. Although these cells have many protrusions that arise spontaneously around the cell periphery, they are still capable of effective directional chemotaxis, as these lateral pseudopods are less persistent than those at the leading edge.…”
Section: Cgmp-signalingmentioning
confidence: 99%